Il signor Erminio Ekdal and the first translation of "The Wild Duck": domesticating Henrik Ibsen for late Nineteenth-Century Italy - D'Amico, Giuliano (Nordicum-Mediterraneum, 2006)
The article focuses on the first Italian translation of Henrik Ibsen's "Vildanden" ("The Wild Duck") made by Enrico Polese Santarnecchi and Paolo Rindler in 1891. The emphasis is on how the translators domesticated the character of Hjalmar Ekdal, making him look closer to an authoritarian, Italian man rather than the lazy husband Ibsen depicted. This had a clear impact on the way the play was received in Italy, and has its foundations in a cultural milieu which Polese knew well and which he felt was unable to accept the sharpest and most sarcastic aspects of the original play.